2012
DOI: 10.1002/jsfa.6004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing conditions on the nutritive value of canola meal and presscake. Comparison of the yellow and brown‐seeded canola meal with the brown‐seeded canola presscake

Abstract: CPC_B had lower protein but higher oil content than canola meal and is a potential high-energy supplement source for ruminants. CM_Y had higher crude protein, digestible and metabolizable energy values and low fiber than CM_B. In plant breeding, selection programs are geared towards yellow-seeded varieties in order to improve the nutritive value of canola meal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 36 publications
11
44
3
1
Order By: Relevance
“…Pelleted samples were not different from the unprocessed mash in regards to carbohydrate fractions either. Theodoridou and Yu (2013b) observed that CA and CB were decreased but CC was increased when canola presscake was desolventizing-toasted. However, pelleting under different conditioning temperatures and time had no effect on carbohydrate fractions of canola meal in our study.…”
Section: Tablementioning
confidence: 97%
See 1 more Smart Citation
“…Pelleted samples were not different from the unprocessed mash in regards to carbohydrate fractions either. Theodoridou and Yu (2013b) observed that CA and CB were decreased but CC was increased when canola presscake was desolventizing-toasted. However, pelleting under different conditioning temperatures and time had no effect on carbohydrate fractions of canola meal in our study.…”
Section: Tablementioning
confidence: 97%
“…The ratio of amide I to amide II can be significantly affected by feed materials, heat processing, and gene transformation (Liu et al, 2012). Theodoridou and Yu (2013b) observed that canola meal had a lower amide I to amide II area ratio than canola presscake, indicating that the area ratio was reduced after desolventizing-toasting during canola processing. However, Samadi et al (2013) indicated that no difference in the area ratio of amide I to amide II was observed when autoclaved (121°C; 1 h) and roasted (120°C; 1 h) canola seeds were compared with unprocessed canola seeds.…”
Section: Effects Of Conditioning Temperature and Time On Protein Molementioning
confidence: 99%
“…Theodoridou and Yu [ 91 ] evaluated the effect of processing conditions on the nutritive value of canola meal and reported significant differences between CM from black- and yellow-seeded B. napus for the basic nutrients, except ash. The differences between yellow and black canola included NDF, ADF, CP, and condensed tannins.…”
Section: Introductionmentioning
confidence: 99%
“…Canola meal, a co-product from bio-oil extraction processing of canola seed, has high CP content and premium protein quality because it contains low concentrations (<30 µmol) of antinutritional compounds called glucosinolates (Theodoridou and Yu, 2013). Therefore canola meal is used in both monogastric and ruminant diets (Newkirk, 2009a,b) and together with rapeseed meal is the second most traded protein source in the global animal feed market (Newkirk, 2009a,b;Heendeniya et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the nutritional values of canola meal for dairy cows have been extensively studied (Heendeniya et al, 2012;Theodoridou and Yu, 2013), information about the effects of conditioning temperature and time during the pelleting on the nutritional value of processed meal is insufficient. Specifically, the digestible NDF in canola meal is an important factor contributing to the energy content of canola meal; however, little attention has been paid to the effect of different processing conditions on NDF availability of canola meal.…”
Section: Introductionmentioning
confidence: 99%